Catalyst-Dependent Chemoselectivity in the Dirhodium-Catalyzed Cyclization Reactions Between Enodiazoacetamide and Nitrosoarene: A Theoretical Study - Zhang, Yan; Yang, Yongsheng; Zhu, Ruyu; Wang, Xingyu; Xue, Ying (Frontiers in Chemistry, 2019)
N-O heterocycle compounds play an important role in various fields. Doyle et al. (Cheng et al., 2017) have recently reported an efficient catalyst-controlled selective cyclization reactions of tert-butyldimethylsilyl (TBS)-protected enoldiazoacetamides with nitrosoarenes in which the multifunctionalized products 5-isoxazolones and 1,3-oxazin-4-ones were formed through [3 + 2]- and [5 + 1]-cyclizations using Rh2(oct)4 and Rh2(cap)4 as catalysts, respectively. The present work studied the mechanism of the reactions in question and the origins of the catalyst-dependent chemoselectivity by the density functional theory (DFT) calculations at the M06-D3/SMD/6-311+G(d,p)//B3LYP-D3/6-31G(d,p) level of theory. The computed results illustrate the importance of the different dirhodium catalysts to gain diversified N-O heterocycle compounds and suggest the specific interaction between the reactants by the real catalyst model. Meanwhile, it is the steric hindrance and electronic effect of the ligands of dirhodium catalysts that control the reaction mechanism. Furthermore, the other auxiliary theoretical analysis, natural bond orbital calculation and distortion/interaction analysis, make the electronic effects and steric hindrance more distinct.